Dynamics of early stage fishes associated with selected warm temperate estuaries in South Africa - Strydom, Nadine Amelia (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2002)
Early stage fishes, namely larvae and early juveniles, were collected from 12 estuaries and associated habitats in the warm temperate region of South Africa between July 1998 and December 2000. This study served to provide new information and expand on existing knowledge of early stage fish assemblages associated with various types of Eastern Cape estuaries. A total of 65 536 predominantly postflexion fish larvae were collected. Together with early juveniles, taxa comprised 72 species from 25 teleost fish families. Surf zones associated with two intermittently open estuaries showed that estuary-dependent marine species predominated in this zone. Early stage fishes responded positively during natural estuary opening events and concentrated along the estuary outflow plume, suggesting that cueing from estuary and/or river water may be taking place. A habitat study in the Swartkops Estuary, using light traps, showed that newly recruited larval fishes concentrated along the margins of the estuary and unlike their older juvenile counterparts, were poorly represented in eelgrass beds. A multi-estuary comparison, including seven permanently open and five intermittently open estuaries, indicated that early stage fish assemblages were more diverse than indicated by past investigations. Early stage fishes were also shown to concentrate in the mesohaline regions of these estuaries. Studies of estuaries with altered freshwater flow regimes were also included in the research. A regulated release of dam water in the euhaline Kromme Estuary failed to induce a cueing response from estuary-dependent marine fish larvae. This project showed that large amounts of freshwater are required to reverse the negative effects of river impoundments. The release study did show that estuary-resident fishes were sensitive to small natural pulses of freshwater and responded by spawning. However, excessive river supply through an inter-basin water transfer scheme was shown to have a flushing effect on the larvae and early juveniles of the estuary-resident Gilchristella aestuaria in the upper reaches of the Great Fish Estuary. This effect was evident in comparisons with the freshwater starved Kariega Estuary where concentrations of G. aestuaria, a species usually more abundant in freshwater rich estuaries, were considerably higher. This finding suggests that freshwater minima and maxima be considered when assessing and managing estuarine systems.
Keywords: Estuarine fishes -- South Africa; Fishes -- Infancy -- South Africa; Estuarine ecology -- South Africa